Evaluation of wheat genotypes for yield potential under combined drought and heat stress conditions - Devi, Suman; Singh, Vikram; ., Naresh (Journal of Cereal Research, 2025)
The combined effects of drought and heat stress severely impact the potential of crop yield. The present study was conducted to determine the tolerant genotypes among 80 wheat genotypes for combined drought and heat stress based on several stress indices. Results showed that grain yield under normal and combined stressed environments was significantly and positively correlated with stress tolerance index (STI) whereas indices like stress susceptibility index (SSI), tolerance (TOL) and reduction (RED) had negative and significant association with grain yield under stressed conditions and significant positive correlation with grain yield under normal conditions. Based on the stress tolerance index, genotypes RW5, WH1142, PBW773, GW463, HD3086 and UP2981 were identified as high yielding as well as stress tolerant, while C306, HD2888, GW477, HD3043, DBW173, JWS825 and MP3288 are promising genotypes to be cultivated under combined drought and heat stress conditions based on stress susceptibility index, tolerance and reduction. The selected genotypes can be further utilized in wheat breeding programmes to develop tolerant cultivars for combined drought and heath stress.